Management Training for Village Owned Enterprises in dealing with Covid-19 Impact: A Story from Candi District in Sidoarjo, Indonesia - Renny Oktafia; Diah Krisnaningsih; Lailatul Fitriani; Mahilda Anastasia Putri (Universitas Muhammadiyah Sidoarjo, 2021)
The village-owned enterprises (BUMDesa) in Sidoarjo namely Sukses Bersama. Currently in the process of improving financial management. Where these partners have an obstacle, namely the problem of unorganized financial management. With the change of management, as well as the presence of Covid-19, which makes financial management less organized in BUMDesa Sukses Bersama. This then makes the proposer choose a partner, and tries to help the problems faced by the partner. Therefore, to improve financial management in BUMDesa Sukses Bersama, BUMDesa administrators and managers need to carry out financial record training. In carrying out these activities, it is necessary to follow several stages, namely the needs analysis stage, the training design stage, the implementation stage, the results testing stage, the assistance and maintenance stage. In this activity more than 50% of BUMDesa's financial management insights have understood the training activities provided. This shows that there has been a significant increase in the ability of BUMDesa administrators in managing finances in their institutions after participating in and implementing training materials.